Approaches to quantify radioligands that wash out slowly from target organs - Hirvonen, Jussi; Terry, Garth E.; Halldin, Christer; Pike, Victor W.; Innis, Robert B. (European journal of nuclear medicine and molecular imaging, 2010)
As a general approach to radioligands with slow kinetics, studies in animals should be used to determine key pharmacological properties, like reversibility, of the radio-ligand; that long scans (and sometimes atypically long scans) be used to identify slow rate constants; and that retest studies can be unusually useful to identify sources of error in measurements of brain uptake and the concentration of radioligand in plasma, as well as in distribution volume, which is a ratio of brain to plasma measurements.